Multidrug-resistant patients receiving treatment in Niger who are infected with M. tuberculosis Cameroon family convert faster in smear and culture than those with M. tuberculosis Ghana family. (May 2020) - Ejo, Mebrat; Hassane-Harouna, Souleymane; Souleymane, Mahamadou Bassirou; Lempens, Pauline; Dockx, Jeroen; Uwizeye, Cecile; De Rijk, Pim; Decroo, Tom; Diro, Ermias; Torrea, Gabriela; Rigouts, Leen; Piubello, Alberto; et al.
Abstract: In this study, we analyzed the M. tuberculosis complex (MTBc) population structure among multidrug-resistant TB (MDR-TB) patients in Niger and tested whether the Cameroon family displayed a slower response to MDR-TB treatment. We genotyped baseline clinical isolates that had been collected from pulmonary MDR-TB patients recruited consecutively between 2008 and 2016 in Niger. Spoligotyping was used to analyze the genetic diversity of mycobacterial lineages, and Kaplan Meier's analysis to compare treatment outcomes. A total of 222 MTBc isolates were genotyped; 204 (91, 9%) were identified as the Euro-American L4 lineage, with the Ghana family (106, 47, 4%) and the Cameroon family (63, 28, 4%) being predominant. Patients infected by Cameroon family isolates 61(96, 8%) showed faster conversion (log-rank p < 0.01) than those infected with Ghana family isolates (91, 5%), and were more likely to experience favorable outcome (adjusted odds ratio [aOR] 4.4; 95%CI 1.1–17.9]; p = 0.015). We found no association between MTBc families and second-line drug resistance profiles (p > 0.05). Our findings show that MDR-TB in Niger is caused by major spoligotypes of the Euro-American L4; with more rapid smear and culture conversion in patients infected with the Cameroon family. These first insights may alert clinicians that slow conversion may be associated with the type of infecting strain. Highlights: Euro-American L4 predominate in the population structure of MDR-TB strains in Niger, mainly the Ghana and Cameroon families. On the Short Treatment Regimen, the median time to sputum smear and culture conversion was two months. Smear and culture conversion was faster for patients infected with Cameroon family than for patients with the Ghana family.